1982
DOI: 10.1002/aja.1001650402
|View full text |Cite
|
Sign up to set email alerts
|

Vasculature of the mouse, rat, and rabbit testis‐epididymis

Abstract: The arrangement of blood vessels serving the testis-epididymis vas investigated microscopically in the mouse, rat, and rabbit. Blood vessels were visualized by infusing liquid silicone rubber into the vessels and subsequently clearing the surrounding tissue. Comprehensive illustrations of the vasculature were prepared from three-dimensional examinations. Arterial and venous vessels serving the testis-epididymis follow similar routes in all three species. However, the arrangements and characteristics of the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
32
2

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 29 publications
7
32
2
Order By: Relevance
“…The cauda epididymis and vas deferens lie on the abdominal side of the blood-testis barrier in mice and receive their blood supply predominantly from branches of the deferential artery (22). This is anterior to the blood-testis barrier, and the vas deferens subsequently receives similar blood to other genitourinary and visceral organs.…”
Section: Generation Of Doublementioning
confidence: 99%
“…The cauda epididymis and vas deferens lie on the abdominal side of the blood-testis barrier in mice and receive their blood supply predominantly from branches of the deferential artery (22). This is anterior to the blood-testis barrier, and the vas deferens subsequently receives similar blood to other genitourinary and visceral organs.…”
Section: Generation Of Doublementioning
confidence: 99%
“…This problem has been studied, to a much lesser degree, in the mouse (Harrison 1949;Harrison and Weiner 1949;Froud 1959;Suzuki 1982;Chubb and Desjardins 1982), the guinea pig (Cooper and Schiller 1975), the golden hamster (Michel 1959) and in the rabbit (Harrison 1949;Harrison and Weiner 1949;Chubb and Desjardins 1982).…”
Section: Arteries Testis Epididymis Spermatic Duct Rabbitmentioning
confidence: 99%
“…Similarly, in laboratory animals such study is necessary for experiments which, to a greater or lesser degree, provide knowledge which could be applied not only to domestic mammals, but also to man. Examples include the study of the effect of heavy metals on the testicular parenchyma, the effect of ionizing radiation, the effect of some medicaments, disorders in the circulation of the blood, as well as various experimental surgical interventions.Among laboratory animals, perhaps the vascularization of the rat testis has been studied the most ( H a r r i s o n 1949; H a r r i s o n and W e i n e r 1949; K o r m a n o 1967; V r z g u l o v á and Hajovská 1968;Hebel and Stromberg 1976;Chubb and Desjardins 1982;Melman et al 1985). This problem has been studied, to a much lesser degree, in the mouse (Harrison 1949;Harrison and Weiner 1949;Froud 1959;Suzuki 1982;Chubb and Desjardins 1982), the guinea pig (Cooper and Schiller 1975), the golden hamster (Michel 1959) and in the rabbit (Harrison 1949;Harrison and Weiner 1949;Chubb and Desjardins 1982).…”
mentioning
confidence: 99%
“…Epididymis segment differences have also been noted in the bull (Hees et al, 1989), boar (Stoffel et al, 1990), mouse (Suzuki, 1982;Abe et al, 1984), rat, rabbit (Chubb and Desjardins, 1982), and man (Kormano and Reijonen, 1976). Stoffel et al (1990), in a study of the boar, observed differences in the organization of the epididymis capillary networks of the caput, as compared to those of the corpus-cauda segments.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, the microvasculature of the epididymis, and the absorptive and secretive processes of the epididymis epithelium are morphofunctional prerequisites for the capacity of sperm to fertilize. Past studies of the epididymis microvasculature have mostly focused on laboratory mammals (Clavert et al, 1980;Chubb and Desjardins, 1982;Suzuki, 1982;Abe et al, 1984;Markey and Meyer, 1992), large breeding mammals (Hees et al, 1989;Stoffel et al, 1990), and man (Kormano and Reijonen, 1976). However, few of these studies dealt with species exhibiting seasonal sexual activity, and they revealed very little regarding the role that vascular structures play in the regulation of nutrition and hormone exchanges.…”
mentioning
confidence: 99%